1985
DOI: 10.1016/0378-1097(85)90106-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nikkomycin on chitin spine formation in the diatom Thalassiosira fluviatilis, and observations on its peptide uptake

Abstract: The nucleoside antibiotic nikkomycin inhibited the formation of β‐chitin spines by the diatom Thalassiosira fluviatilis, and slowed its growth rate, at a minimum inhibitory concentration of 4 μM. The resulting chitin‐free cells sedimented much more rapidly in the cultures than did control cells. The uptake of nikkomycin was not antagonised by the dipeptides Gly‐Val, Met‐Met or Phe‐Leu. Of Six dipeptides tested, Met‐Met, Phe‐Leu and Tyr‐Gly were taken up by the diatoms, but Gly‐Gly, Gly‐Val and Ala‐Ala were not. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the case of C. albicans in the presence of nikkomycin, a potent competitive inhibitor of chitin synthase (Gooday et al, 1985;Gow & Selitrennikoff, 1984;Hector & Braun, 1986), synthesis of this skeleton was severely reduced (Table 1, Fig. 3) with the formation of an abnormal wall characterized by greater amounts of S-glucan and very low concentrations of I-glucan and mannoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of C. albicans in the presence of nikkomycin, a potent competitive inhibitor of chitin synthase (Gooday et al, 1985;Gow & Selitrennikoff, 1984;Hector & Braun, 1986), synthesis of this skeleton was severely reduced (Table 1, Fig. 3) with the formation of an abnormal wall characterized by greater amounts of S-glucan and very low concentrations of I-glucan and mannoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the centric planktonic diatom Cyclotella synthesizes long fibrillar chitinous appendages (Blackwell et al 1967), that slow down the sinking velocity of the cells (Walsby and Xypolyta 1977). It was reported (Gooday et al 1985) that the formation of β-chitin spines by the diatoms as well as their growth rates can be inhibited by the nucleoside antibiotic nikkomycin even at a minimum inhibitory concentration of 4 μM. In contrast to control cells, the chitin-free cells, which had been treated with nantibiotics, sedimented much more rapidly (Gooday et al 1985).These chitinous spines are extremely stiff and crystalline and occur as up to 50 nm wide ribbons composed of parallel oriented nanofibrils which diameters between 5 and 30 nm.…”
Section: Chitin In Diatomsmentioning
confidence: 99%
“…It was reported (Gooday et al 1985) that the formation of β-chitin spines by the diatoms as well as their growth rates can be inhibited by the nucleoside antibiotic nikkomycin even at a minimum inhibitory concentration of 4 μM. In contrast to control cells, the chitin-free cells, which had been treated with nantibiotics, sedimented much more rapidly (Gooday et al 1985).These chitinous spines are extremely stiff and crystalline and occur as up to 50 nm wide ribbons composed of parallel oriented nanofibrils which diameters between 5 and 30 nm. It was observed that diatom chitin forms broader ribbons and is more crystalline than those of fungal, or arthropodal origin (Herth and Zugenmaier 1977).…”
Section: Chitin In Diatomsmentioning
confidence: 99%
“…All flasks were incubated at 25°C. Uptake of nikkomycin Z was assessed at hourly intervals over a period of 7 h and again 24 h after addition of the antibiotic to the flasks by determining spectrophotometrically the amount of nikkomycin Z remaining in each flask (Gooday et al, 1985). Samples of liquid medium were removed from each flask, filtered to remove any particulate material which might interfere with absorbance readings, and transferred to quartz cuvettes.…”
Section: Uptake Of Nikkomycin Zmentioning
confidence: 99%
“…Di-L-alanine (Ala-Ala) or tri-L-alanine (Ala-AlaAla) (Sigma) were then added to the flasks at an initial concentration of 100 mol. The concentration of di-or tripeptide in each flask was determined at hourly intervals over a period of 5 h and again 24 h after addition of either peptide using the fluorescamine technique (Perrett et al, 1975;Gooday et al, 1985). Samples (1 ml) of the medium removed from each flask were filtered to remove particulate material and 50-l samples of filtrate reacted with fluorescamine at pH 6.2.…”
Section: Uptake Of Di-and Tripeptidesmentioning
confidence: 99%